2015
DOI: 10.1371/journal.pone.0141751
|View full text |Cite
|
Sign up to set email alerts
|

Critical Parameters of the In Vitro Method of Vascular Smooth Muscle Cell Calcification

Abstract: BackgroundVascular calcification (VC) is primarily studied using cultures of vascular smooth muscle cells. However, the use of very different protocols and extreme conditions can provide findings unrelated to VC. In this work we aimed to determine the critical experimental parameters that affect calcification in vitro and to determine the relevance to calcification in vivo.Experimental Procedures and ResultsRat VSMC calcification in vitro was studied using different concentrations of fetal calf serum, calcium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 29 publications
4
49
0
Order By: Relevance
“…15 Third, with the logical objective of simplifying this complexity, the scientific community has been using in vitro methods of calcification that, unfortunately, were unrelated to cell-mediated ectopic calcification. 14 In this work, our purpose has been to disentangle the complexity of VC by using an experimental approach that has sufficient clarity: we have focused on the very early pathogenic steps, while assuming that the complexity of advanced calcification is a consequence of an increasing and self-complicating morbid process. We chose the evolution of artery calcium content as from nephrectomy as the baseline for a time-course study of pathogenic events until a frank calcification was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Third, with the logical objective of simplifying this complexity, the scientific community has been using in vitro methods of calcification that, unfortunately, were unrelated to cell-mediated ectopic calcification. 14 In this work, our purpose has been to disentangle the complexity of VC by using an experimental approach that has sufficient clarity: we have focused on the very early pathogenic steps, while assuming that the complexity of advanced calcification is a consequence of an increasing and self-complicating morbid process. We chose the evolution of artery calcium content as from nephrectomy as the baseline for a time-course study of pathogenic events until a frank calcification was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In the search for a less complex model, the in vitro methods of Pi-induced calcification were discarded. 14 Therefore, for the sake of simplicity we have studied the very early stages of aortic calcification during CKD using the 5/6-nephrectomized (NX) rat model, in which rats were fed a Pi-rich diet. The aorta calcium content, the specific gene expression changes, serum and urine parameters, and protein expression and activities were analyzed at different times as from nephrectomy.…”
Section: Introductionmentioning
confidence: 99%
“…In line with our findings, Reynold et al [25] found that calcium was a stronger inducer of calcification than phosphate in an in vitro study of aortic rings from humans exposed to various phosphate and calcium concentrations with CPP held constant. However, in vitro studies of the pathophysiology of calcium-phosphate disturbances and vascular calcification, conducted to imitate the conditions of chronic kidney disease with elevated extracellular calcium and phosphate and have been criticised for their un-physiological conditions [26], making extrapolation of these data difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Several inhibitors of mineralization including PP i [102], phosphorylated osteopontin (OPN) [103], matrix Gla protein [104, 105], and fetuin A [106] can prevent apatite formation. The formation of apatite is preceded by a nucleation step [1, 98101, 107] and/or by an intermediate formation of ACP [100, 101, 108, 109]. Apatite in a crystalline phase is induced by a nucleation step, even if it is generated from ACP.…”
Section: Properties and Functions Of Mvsmentioning
confidence: 99%